1, 2, 3-Triazole-based sequence-defined oligomers and polymers. Issue 18 (19th April 2021) - Wang, Xiaojun; Zhang, Xueyan; Ding, Shengtao
Abstract : This review offers a summary on the advances in the construction of 1, 2, 3-triazole-based sequence-defined oligomers and polymers through MAAC-based ISG or IEG strategies. Abstract : Mimicking nature to create polymers with well-defined sequences and precise chain lengths for multitudinous applications is an increasingly attractive but challenging field. In the absence of biological machineries, robust and efficient chemical reactions are important for the construction of artificial sequence-defined polymers. Due to the specific characteristics of the 1, 2, 3-triazole skeleton and its facile accessibility from the "click" reaction of an azide with an alkyne, research on the synthesis and application of sequence-defined polymers involving 1, 2, 3-triazole substructures has attracted much attention in the recent two decades. This review summarizes the developments in this field from two parts: (i) creation of biomimetic oligomers in which 1, 2, 3-triazoles were used as amide bioisosteres or as linkers between natural monomers and (ii) establishment of diverse efficient synthetic strategies on the basis of azide–alkyne cycloaddition reactions and their utilization in the construction of non-biomimetic sequence-defined polytriazoles. Application of these 1, 2, 3-triazole-linked sequence-defined polymers in different areas is also briefly discussed.